Pam2CSK4 (TLR2 agonist) induces periodontal destruction in mice - de Souza, João Antonio Chaves; Magalhães, Fernando Augusto Cintra; de Oliveira, Guilherme Jose Pimentel Lopes; de Molon, Rafael Scaf [UNESP]; Zuanon, José Antonio [UNESP]; de Souza, Pedro Paulo Chaves (FapUNIFESP (SciELO), 2020)
Lipoproteins are important bacterial immunostimulating molecules capable of inducing receptor activator of nuclear factor-κB (RANKL) and osteoclast formation in vitro and in vivo. Although these molecules are present in periodontopathogenic bacteria, their role in periodontitis is not known. In this study, we used Pam2CSK4 (PAM2), a synthetic molecule that mimics bacterial lipoprotein, to investigate the effects of lipoproteins on periodontitis in mice. C57BL/6 male mice were randomly divided into three experimental groups: 1) Negative control group: animals received vehicle injection; 2) Positive control group: animals received injection of Escherichia coli lipopolysaccharide (LPS); 3) PAM2 group: animals received PAM2 injection. All the injections were performed bilaterally every other day into the palatal mucosa between first and second molars. After twenty-four days, the animals were euthanized to assess alveolar bone volume (micro-CT), cellular and extracellular composition in the gingiva (stereometric analysis), and osteoclast numbers (TRAP staining). Treatment with either PAM2 or LPS induced gingival inflammation, as demonstrated by increased infiltration of inflammatory cells and enhanced angiogenesis, associated with a smaller number of fibroblasts and decreased extracellular matrix. Importantly, treatment not only with LPS but also with PAM2 resulted in a larger number of TRAP+ multinucleated osteoclasts and significant loss of alveolar bone. Collectively, our data demonstrate that PAM2 can induce gingival inflammation and bone loss in mice, broadening the avenues of investigation into the role of lipoproteins in the pathogenesis of periodontal disease.
Keywords: Bone and bones; Inflammation; Lipoproteins; Mice; Osteogenesis; Periodontal diseases; Toll-like receptors